Taxonomic review of Manulea (M.) tienmushanica (Daniel), comb. nov., and its allies with descriptions of two new species from mainland China (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V.; Saldaitis, Aidas; Huang, Si-Yao (Zootaxa, 2022)
The Manulea tienmushanica (Daniel, 1954) species group is established, characterised and reviewed. Two new species are described: Manulea (M.) salweena sp. n. (China: Yunnan), and Manulea (M.) diaforetica sp. n. (China: Yunnan). Two new combinations are established: Manulea (M.) tienmushanica (Daniel, 1954), comb. n. and Manulea (M.) nigripuncta (Fang, 2000), comb. n. Adults, male and female genitalia are illustrated.